A Small Cut, a Big Challenge: Pediatric Mucormycosis in an Unexpected Host - Marriam Tanvir (22330462) (2025)
Mucormycosis is an infrequent fungal infection commonly seen in immunocompromised individuals. However, it can also occur in immunocompetent patients, especially following trauma. We present a case of a 15‐month‐old girl with increasing swelling and redness in her left eye after a minor traumatic injury. Imaging showed sinusitis with orbital involvement. Histopathology validated the diagnosis of mucormycosis caused by Rhizopus species. The patient had emergency surgery, followed by antifungal and antibiotic therapy. Despite febrile reactions to the treatment, the infection was managed, and the patient was discharged after 2 months. This case highlights the importance of considering mucormycosis in immunocompetent patients with unexplained ocular symptoms after trauma. Early diagnosis and aggressive treatment are essential for improving outcomes, especially in pediatric patients. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.70176